Վրաստանի կառավարությունը և Սոչիի շրջանի համշենահայ համայնքը (1918-1920 թթ.) - Մաիլյան, Բենիամին («Զանգակ - 97»)
After proclamation of independence of Georgia, Sochi district was ruled by force, which was under control of Georgian national govemment. Sochi's status was not finally juridically legalized. The question of border evoked military conflict between Georgia and Russian "White" movement from suffered Hamshin Armenian population of the Sochi district. The violence of georgian troops had such result as rebellion local Hamshin Armenians' in the February of 1919.
Keywords: Ազգագրություն; Սփյուռքահայ գաղթօջախներ